Understanding the Gastro-Musculoskeletal Loop: A Case of GERD-Induced Postural Adaptations Leading to Cervical Spondylosis - Thiyagarajan, Alagappan; Palaniswamy, Vijayakumar; Shaikh, Hanzala J; Alagappan, Ramalingam (INTI International University, 2026)
Gastroesophageal reflux disease (GERD) is a gastrointestinal disorder that can induce compensatory postural adaptations, potentially contributing to cervical spondylosis. Understanding this gastro-musculoskeletal relationship is crucial for holistic patient management. A 40-year-old male with chronic GERD and cervical spondylosis underwent an 8-week physiotherapy program focusing on postural correction, strengthening of deep cervical flexors and scapular stabilizers, stretching of tight anterior chest muscles, and diaphragmatic breathing exercises. Concurrent GERD management included lifestyle modifications and prescribed medications. Outcome measures included cervical range of motion, pain intensity, and postural assessment scores. Over 8 weeks, the patient demonstrated progressive improvement in cervical mobility, reduction in neck pain, and correction of forward head posture and scapular protraction. Integration of physiotherapy and GERD management contributed to symptom relief and functional recovery. This case highlights the bidirectional gastro-musculoskeletal loop, where GERD-induced postural adaptations can predispose to cervical spondylosis. Combined physiotherapy and GERD management can effectively improve musculoskeletal function and patient quality of life. Early recognition and interdisciplinary intervention are recommended for optimal outcomes